From science-and-religion to science-engaged theology - Leidenhag, Joanna (Theology, 2024)
Science-engaged theology has become all the rage lately. But what is ‘science-engaged theology’ and how does it relate to the pre-existing field of science-and-religion? This article argues that the field of science-and-religion and science-engaged theology seek to answer quite different questions. Science-and-religion asks about the relationship between separate disciplines or beliefs. Science-engaged theology asks how scientific research can be a source for Christian thought and practice. In so doing, science-engaged theology destabilizes the concepts ‘science’, ‘religion’ and ‘theology’ upon which both these approaches depend.